Glucose-6-Phosphatase Catalytic Subunit 3 (G6PC3) Deficiency Associated With Autoinflammatory Complications - Mistry, Anoop; Scambler, Thomas; Parry, David; Wood, Mark; Barcenas-Morales, Gabriela; Carter, Clive; Doffinger, Rainer; Savic, Sinisa (Frontiers in Immunology, 2017)
G6PC3 deficiency typically causes severe congenital neutropenia, associated with susceptibility to infections, cardiac and urogenital abnormalities. However, here we describe two boys of Pakistani origin who were found to have G6PC3 deficiency due to c130. C>T mutation, but who have clinical phenotypes which are typical for a systemic autoinflammatory syndrome. The index case presented with combination of unexplained fevers, severe mucosal ulcers, abdominal symptoms and inflammatory arthritis. He eventually fully responded to anti-TNF therapy. In this study, we show that compared to healthy controls, neutrophils and monocytes from patients have reduced glycolytic reserve. Considering that healthy myeloid cells have been shown to switch their metabolic pathways to glycolysis in response to inflammatory cues, we studied what impact this might have on production of the inflammatory cytokines. We have demonstrated that patients’ monocytes, in response to LPS, show significantly increased production of IL-1ß and IL-18, which is NLRP3 inflammasome dependent. Furthermore, additional whole blood assays, have also shown an enhanced production of IL-6 and TNF from the patients’ cells. These cases provide further proof that autoinflammatory complications are also seen within the spectrum of primary immune deficiencies, and resulting from a wider dysregulation of the immune responses.